2019
DOI: 10.1038/s41419-019-2067-2
|View full text |Cite
|
Sign up to set email alerts
|

PITPNA-AS1 abrogates the inhibition of miR-876-5p on WNT5A to facilitate hepatocellular carcinoma progression

Abstract: LncRNA PITPNA-AS1 was a newly identified lncRNA which has never been studied in cancers. Whether PITPNA-AS1 participated in the development of hepatocellular carcinoma (HCC) is obscure. Given the coaction of lncRNAs and miRNAs to carcinogenesis, the purpose of the present research is to inquire how PITPNA-AS1 affects HCC progression. Firstly, PITPNA-AS1 was observed to be heightened in HCC tissues. Then function assays proved that overexpressing or silencing PITPNA-AS1 could manipulate the proliferation and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…PiTPna-aS1 is a newly reported lncrna, which is located on chromosome 17p13.3 (11). a previous study revealed that PiTPna-aS1 could facilitate the progression of hepatocellular carcinoma via the regulation of the mir-876-5p/WnT5a signaling pathway (11). analyzing data from TcGa database, the present results demonstrated that the expression of PITPNA-AS1 in NSCLC tissues was significantly increased compared with that in the adjacent non-tumor tissues.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…PiTPna-aS1 is a newly reported lncrna, which is located on chromosome 17p13.3 (11). a previous study revealed that PiTPna-aS1 could facilitate the progression of hepatocellular carcinoma via the regulation of the mir-876-5p/WnT5a signaling pathway (11). analyzing data from TcGa database, the present results demonstrated that the expression of PITPNA-AS1 in NSCLC tissues was significantly increased compared with that in the adjacent non-tumor tissues.…”
Section: Discussionsupporting
confidence: 54%
“…PiTPna-aS1 is a newly reported lncrna, which is located on chromosome 17p13.3 (11). a previous study revealed that PiTPna-aS1 could facilitate the progression of hepatocellular carcinoma via the regulation of the mir-876-5p/WnT5a signaling pathway (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiR-876-5p was reported to have different roles in different types of tumorigenesis. For example, PITPNA-AS1 abrogated the inhibition of miR-876-5p on WNT5A to facilitate HCC progression [ 34 , 35 ]. MicroRNA-876-5p inhibited cell proliferation, migration and invasion by targeting c-Met in osteosarcoma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%